Stakeholder Analysis of Small-Scale Fisheries in Bunyu Island, North Kalimantan, Indonesia - Taufiq Romdoni; Muhammad Firdaus; M. Gandri Haryono; Awang Pradana; Yushra; Muhammad Yusfi Yusuf; Ardy Andreas Bernard Kase; Dian Islamia Muhtar (Universitas Islam Lamongan, 2026)
Small-scale fisheries in Bunyu Island, North Kalimantan, hold a strategic position in supporting Indonesia’s maritime border economy. Various stakeholders are involved in the management of small-scale fisheries in the island. The objective of this study is to analyze stakeholders engaged in small-scale fisheries in Bunyu Island, North Kalimantan, Indonesia. A survey method was employed, with data collection conducted from July to August 2025. Respondents were determined using a purposive sampling technique, comprising parties directly involved in small-scale fisheries on the island. The analysis employed stakeholder categorization, stakeholder analysis by influence-interest matrix, and actor linkage mapping to examine stakeholder positions and interactions. The findings indicate that 14 stakeholders are engaged in the management of fisheries in Bunyu Island. The Marine and Fisheries Office of North Kalimantan hold both high interest and influence due to its authority in fisheries management. Fishers, while having high interest, exhibit relatively low influence in the policy-making process. These findings highlight the presence of power asymmetry and predominantly top-down governance structure. Academic institutions play a role by providing research and recommendations to support fisheries management. To promote collaborative governance, the Provincial Marine and Fisheries Office should institutionalize fisher participation in decision-making forums.